Nutritional status as predictor of quality of life in patients undergoing hemodialysis - Marina Abelha Barreto; Monica Cattafesta; Edson Theodoro dos Santos Neto; Luciane Bresciani Salaroli (Universidade Federal do Estado do Rio de Janeiro, 2022)
ABSTRACT Objective: to evaluate the association between quality of life and nutritional status of hemodialysis patients, according to anthropometric and biochemical measurements. Methods: cross-sectional study conducted with 1,024 patients from 11 hemodialysis centers in a metropolitan region of southeastern Brazil. Results: through multiple linear regression, the nutritional predictors of each domain of quality of life were identified. We highlight serum albumin, Body Mass Index (BMI) and waist circumference, among the measures associated with both physical and mental health in this population. Conclusion: inadequate nutritional status is associated with worse physical and mental quality of life in hemodialysis individuals. In addition to monitoring the nutritional status, nutritional assessment predicts quality of life and becomes a fundamental tool for a better health outcome, since low quality of life is one of the main problems in this population. DESCRIPTORS: Quality of life related to health; Renal replacement therapy; Nutritional assessment.